Shisha Smoking Habit among Dental School Students in the United Arab Emirates: Enabling Factors and Barriers - Natheer H. Al-Rawi; Ahmed S. Alnuaimi; Asmaa T. Uthman (International Journal of Dentistry)
Objectives. The objective of the present study was to assess shisha smoking among dental school students in Sharjah, United Arab Emirates (UAE). In addition, the role of suggested barriers and enabling factors in shisha smoking was also evaluated. Methods. A cross-sectional questionnaire-based survey was conducted at the College of Dental Medicine, University of Sharjah, between February and May 2016. The questions were adapted from previously published water pipe smoking studies. The collected data were analyzed to identify the relationship between shisha smoking and sociodemographic characteristics. Relevant questions were further categorized as enabling factors and barriers for shisha smoking. Results. Three enabling questionnaire items related to social environment were significantly associated with an increased risk of being a current smoker. The most powerful is peer pressure (“friends smoke shisha”), which increased the odds ratio of shisha smoking 11.3 times, followed by smoker sibling with increase in odd ratio by 4.52 times, then the belief of social acceptance with increase in odd ratio by 4.31 times. Conclusion. Shisha smoking is a serious problem among university students. Any intervention program in the university curricula should consider teaching students that shisha is no less risky than cigarettes and is addictive.